Paradigma Positivisme Hukum John Austin Di Era Posmodernisme - Setiawan, Adam; Ismail, Rezky Robiatul Aisyiah (Universitas Brawijaya, 2023)
The purpose of this research is to find out how the legal positivism paradigm of John Austin in the era of postmodernism and explain the relevance of legal positivism in law enforcement in Indonesia. This research uses method of philosophy of law. The results are that John Austin's legal positivism paradigm in the era of postmodernism is increasingly losing its way because it is exclusive. The legal positivism paradigm cannot be a guidance in law because the shortcomings of the legal positivism paradigm include the legal positivism paradigm constructed by Austin that is unable to accommodate important aspects outside the specified elements such as ethical, moral, and religious elements. Although, the paradigm of legal positivism in Indonesia has become the main point of law enforcement because of the continental European legal tradition. However, in practice the legal positivism paradigm is not compatible with the existing legal patterns in Indonesia because: (1) Indonesian society is heterogeneous; (2) Social, political, and economic developments are transforming so rapidly that the law is lagging behind; and (3) Indonesian people are religious but have no absolute ideology of religion.